Relación de las habilidades intrapersonales e interpersonales de los padres con las habilidades de interacción social de los niños y niñas de cinco años en la institución educativa inicial N° 305 – Monterrey del distrito de Nueva Cajamarca en el año 2010 - Sánchez Manosalva, Naira Judith (2011)
The realized study has had as aim determine the relation of the skills intrapersonales and interpersonal of the parents with the skills of social interaction of the children and five-year-old girls in the Educational lnitial lnstitution N° 305 - Monterrey of the district of New Cajamarca in the year 2010. The investigation of type correlacional, of level explicative has been realized by 30 children and girls; and, with 30 parents. Across the technology of the survey I apply the Scale of skills intrapersonales and interpersonal, directed to the family parents to gather information about the aptitude to lead his own lite and to understand the others. By means of the interview there was applied the Scale of skills of social interaction, directed to the children to gather information about the aspects necessary for the personal and interpersonal well-being. The gathered information was processed by means of the distribution of frequencies and the coefficient of Pearson's correlation, the test of hypothesis realized by means of the comparison of Pearson's coefficient with the parameters of correlation, considering that the relation is direct when the coefficient is positive and the relation is inverse when it is negative. In agreement to the coefficient of Pearson's correlation (0,89), directly proportional relation exists between the skills intrapersonales of the parents and the skills of social interaction of the children and five-year-old girls in the Educational lnitial lnstitution N ° 305 - Monterrey of the district of New Cajamarca in the year 2010. In agreement to the coefficient of Pearson's correlation (0,64), directly proportional relation exists between the interpersonal skills of the parents and the skill of interaction social of the children and five-year-old girls in the Educational lnitial lnstitution N ° 305 - Monterrey of_ the district of New Cajamarca in the year 2010.